In vitro activity of bedaquiline against Mycobacterium avium complex. Issue 10 (20th October 2021) - Litvinov, Vitaly; Makarova, Marina; Kudlay, Dmitry; Nikolenko, Nikolai; Mikhailova, Julia
Abstract : Introduction. Nontuberculous mycobacteria (NTM) are widespread in the environment and can cause various diseases in humans, especially immunocompromised patients. Hypothesis. Treatment of diseases caused by NTM is a complicated issue, mainly due to the resistance of the pathogen to most antimicrobial agents. Bedaquiline (Bdq) is now widely used for the treatment of multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB). Aim. The main goal of our study was to evaluate the activity of Bdq against Mycobacterium avium complex (MAC), the most common species among NTM. Methodology. A total of 166 MAC cultures (124 Mycobacterium avium and 42 Mycobacterium intracellulare ) were studied. The minimum inhibitory concentrations (MICs) of Bdq for M. avium and M. intracellulare were obtained by twofold serial dilutions in the Middlebrook 7H9 medium. MIC ranges were determined and the MIC50, MIC90 and ECOFF values were obtained. Results. The MICs in respect of M. avium ranged from 0.003 to 1.0 µg ml −1 ; those for M. intracellulare ranged from 0.003 to 0.5 µg ml −1 . The Bdq MIC50 and MIC90 values were found to be 0.015 and 0.12 µg ml −1, respectively, for M. avium and 0.007 and 0.06 µg ml −1, respectively, for M. intracellulare . The tentative ECOFF values for M. avium and M. intracellulare were 0.12 and 0.06 µg ml −1, respectively. Conclusion. The main bedaquiline susceptibility parameters for MAC strains isolated in the Moscow region were determined.